Proposing new procedures for the management and prevention of foodborne diseases: an Italian experience: New procedures for foodborne disease prevention - Di Federico, Silvia; Maione, Domenico; Cilloni, Silvia; Raschi, Elisa; Montanari, Nadia; Di Ruocco, Salvatore; Rizzi, Simona; Lionetti, Francesca Pia; Bisaccia, Eufemia; Poeta, Antonio; De Vita, Daniela; Bedeschi, Emanuela; et al. (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Foodborne diseases are a public health issue with more than 4,000 outbreaks in 2021 in European Union countries and United Kingdom and their management is important for prevention and controls of outbreaks. Recently, new technological tools and strategies, including whole genome sequencing (WGS), have become available to allow the highest level of discrimination in the investigation of foodborne outbreak. In this study, we presented the updated procedure for assessment of foodborne disease within a community of Northern Italy. Methods: In the Reggio Emilia Local Health Authority (RE-AUSL), foodborne disease monitoring and control are managed by the following health Services: Public Health Unit (SIP); Food Hygiene and Nutrition Service (SIAN) and Official Veterinary Service (SSPV) composing the developed MTA group (‘Gruppo Malattie Trasmesse da Alimenti’). Among the new tools being implemented, there is a shared computerized folder and new related managements procedures available to MTA members only, allocating information regarding any material useful to the MTA group. Results: The main new features of the new procedure are: information sharing in all phases of the management of the infectious episode, integration of the three services through the creation of the MTA group and updated criteria for procedure activation, and finally a dedicated training programme. Conclusions: Timely investigation, management and control of MTA outbreaks is essential for both health and economic reasons. The new features and procedures implemented in this Italian community may allow to identify rapidly the causes of a case or outbreak and better counteract their spread.